Assessment of spatial changes in the duck harvest within the Central Flyway, 1997–2011 - Haugen, Matthew T.; Powell, Larkin A.; Vrtiska, Mark V. (Wildfowl, 2014)
Knowledge of the factors which influence the spatial distribution of duck harvest would be useful to managers when setting dates for the duck hunting seasons. Here we used changes in mean latitude of harvest to represent changes in distribution of duck harvest during the hunting season within the Central Flyway from 1997–2011, derived from harvest data from the U.S. Fish and Wildlife Service Parts Collection Survey. A candidate set of models was developed to represent competing hypotheses of corn availability, weather, water on the landscape, competition via population density, hunting pressure, and regulatory change to explain the variation in harvest distribution of Mallard Anas platyrhynchos, dabbling ducks Anas sp., and diving ducks Aythya sp. The model selection process revealed that hunting pressure, the amount of water on the landscape, and Mallard density best explained the distribution of Mallard harvest. Mallard harvest distributions tended to be further north during wet years of high Mallard densities and low hunting pressure, relative to dry years with high Mallard densities and low hunting pressure. High hunting pressure shifted the spatial distribution of Mallard harvest further south. Regulations had the largest influence on both dabbling (non-Mallard) and diving duck harvest distribution. Dabbling duck harvest distribution was further north under the 2002–2011 frameworks, relative to the 1997–2001 frameworks. During the 2002–2011 frameworks, diving ducks were more likely to be harvested further south early in the season and further north later in the season, relative to 1997–2001 frameworks. Trends in the distribution of harvest should be informative for future harvest management decisions.